Reviews via Mobile: The Role of Mobile Cues and Typographical Errors in Online Review Adoption - Lim, Young-shin; Maslowska, Ewa (Frontiers in Psychology, 2022)
Online consumer reviews are increasingly being written on and posted from mobile devices such that some platforms have started to indicate when this is the case with cues such as “via mobile” (i.e., mobile cue). Reviews from mobile devices differ from those from nonmobile devices; for example, reviews from mobile devices are more likely to include typographical errors. For this study, a web-based experiment was conducted to investigate viewers’ evaluation and adoption of online reviews in regard to a mobile cue and typographical errors. The results indicate an interaction effect between the presence of a mobile cue and typographical errors. When a review did not include typographical errors, the presence of a mobile cue negatively affected the evaluation and adoption of information (i.e., the viewer’s attitude towards the reviewed restaurant). However, the effects of a mobile cue were not significant for a review with typographical errors. Further, the results suggest that the viewer’s perception of the review writing effort and the review’s information usefulness are sequential mediators explaining the mechanism. The findings provide interesting insights into consumers’ perceptions of online reviews in the current media landscape in which the large-scale adoption of mobile devices is a well-recognized phenomenon.